Legal Aspects of City Branding for the Protection of Trademark Rights: City Branding of Ambon City of Music - Fransisca Jallie Pattiruhu (Journal of Law, Politic and Humanities, 2024)
The issue that this paper seeks to address is how the Law 20 of 2016 regulates trademarks and geographical indications in relation to municipal branding. Normalcy in the law is the subject of this study. Law 20 of 2016, which regulates geographical indications and trademarks, is the subject of this study's investigation into the potential consequences of city branding. After then, a statute and a conceptual framework pertaining to trademark registration are used to examine the matter. Following this description, the author has drawn the following conclusions: One thing to keep in mind is that city branding is not specifically addressed in Law No. 20 of 2016, which regulates trademarks and geographical indicators. Second, because it does not contradict with anything that is forbidden or cannot be registered in a trademark registration application, city branding can be specifically registered as a city service or trademark. Thirdly, the city branding of Ambon City, known as “Ambon City of Music,” satisfies the elements of city branding previously mentioned. In addition, the brand “Ambon City of Music” is known among local and national communities as having given birth to or produced many singers and musicians in this city.